(untitled) (Bangladesh Medical Journal, 2019)
Burst Abdomen is a preventable condition in which many risk factors play their role and lead to life threatening complications. This study was carried out to find out various risk factors of burst abdomen following emergency laparotomy, to find out the high risk group of patients for burst abdomen, to determine the predictors of burst abdomen, to prevent the rate of burst abdomen & find out morbidity and mortality of burst abdomen. This cross sectional study was done among 100 cases of burst abdomen occurring in Sir Salimullah Medical College & Mitford Hospital, Dhaka and Dhaka Medical college,Dhaka during the period of July,2011 to December,2011. The patients were admitted for various surgical problems and underwent emergency laparotomy. Burst abdomen was taken into account. Another group of 100 patients who undergone emergency laparotomy but did not develop burst abdomen were also taken into account to make a comparison with the burst group. Patients who undergone elective laparotomy,paediatric age group,patients undergone exploration through mini laparotomy or transverse incision,patients with pregnancy were excluded from the study populations.Patients were assessed by history taking, examination and appropriate investigation before surgery and observed post operatively for any complication. The results were prepared on 100 patients underwent emergency laparotomy in SSMCMH & DMCH. Burst abdomen following emergency laparotomy results from multifactorial causes. The main outcome measure found significant as the risk factors of burst abdomen in this study were peritonitis (95%),anaemia (26%),malnutrition (18%), in the preoperative period; inadequate peritoneal toileting and faulty surgical techniques in the per operative period; and wound infection (62%), postoperative cough (28%), abdominal distension (22%). The result also shows that the rate of burst abdomen is still very high in SSMCMH & DMCH and most of them occur in operations done by trainee surgeons (86%) and in those patients who has 3 or more of the risk factors (44%). We hope this study will arouse awareness and concern about this problem, so that more active steps will be taken for its prevention by identifying the high risk groups. This will certainly reduce the incidence of burst abdomen. Bangladesh Med J. 2017 May; 46 (2): 38-42